A fenomenologia da aquisição da língua estrangeira - Fonseca, Fábio Luiz Socreppa da (2017)
The possibility of being in touch with other cultures through the engagement with communication technology, entertainment experiences, requirement of labor market or cultural enrichment, leads innumerous people into learning foreign languages. The path to learning then is usually based on exchange programs or specialized courses on second language acquisition (it could be in one’s own country or in another whose population is native on that language), options that require large personal and financial investment for that purpose. This cultural and market demand led, in the last century, to the development of different methods for teaching foreign languages. These methodologies understand the experience of speech as an element of empiria or as a product of consciousness, which distant the daily experience from what it is to communicate. The present research is bibliographic and guided by phenomenological references, especially, Maurice Merleau-Ponty, David Le Breton and other authors focused on the discussion of corporeity and embodied language, and it aims to understand the acquisition of the foreign language in the organization of one’s own body and the lived world. The one’s own body is the center of our existence and it is by its corporeal experiences that all knowledge acquisition is apprehended. The movement to comprehend this acquisition takes the experience of speaking the mother tongue and its structural role in one’s formation and its perception of the world. The comprehension of the foreign language is anchored in its appropriation by one’s own body, by its possibility of contact with other cultures and with the speakers of these linguistic horizons, and finally, by the amplification of the understanding about the oneself, lived by the subject in its process of being aware of its own language and culture by the otherness’s perspective. The purpose of this text is to open a new horizon for the understanding and discussion about the experience of speaking a foreign language.